Measurement of the CP violation parameter Aγ in D0→K+K− and D0→π+π− decays - Aaij, Roel; D'Argent, Philippe; Bachmann, Sebastian; Braun, Svende; De Cian, Michel; Comerma-Montells, Albert; Esen, Sevda; Färber, Christian; Gerick, David; Gersabeck, Evelina; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; et al. (Physical review letters, 2017)
Asymmetries in the time-dependent rates of D0→K+K− and D0→π+π− decays are measured in a pp collision data sample collected with the LHCb detector during LHC Run 1, corresponding to an integrated luminosity of 3 fb−1. The asymmetries in effective decay widths between D0 and ¯¯¯D0 decays, sensitive to indirect CP violation, are measured to be AΓ(K+K−)=(−0.30±0.32±0.10)×10−3 and AΓ(π+π−)=(0.46±0.58±0.12)×10−3, where the first uncertainty is statistical and the second systematic. These measurements show no evidence for CP violation and improve on the precision of the previous best measurements by nearly a factor of two.